2017
DOI: 10.1111/jpi.12415
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin enhances neural stem cell differentiation and engraftment by increasing mitochondrial function

Abstract: Neural stem cells (NSCs) are regarded as a promising therapeutic approach to protecting and restoring damaged neurons in neurodegenerative diseases (NDs) such as Parkinson's disease and Alzheimer's disease (PD and AD, respectively). However, new research suggests that NSC differentiation is required to make this strategy effective. Several studies have demonstrated that melatonin increases mature neuronal markers, which reflects NSC differentiation into neurons. Nevertheless, the possible involvement of mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 63 publications
6
53
0
Order By: Relevance
“…Specifically, we found that higher content of melatonin in the tumor microenvironment was associated with less aggressive stage classification and favorable prognosis, which suggested that the melatonergic microenvironment may influence tumor carcinogenesis, prevent the formation of aggressive phenotypes, and therefore result in a decreased risk of death. This is consistent with previous observations that melatonin reduces the susceptibility of gastric mucosal cells to dietary carcinogens through enhanced DNA repair capacity, and inhibits cancer cell proliferation by decreasing DNA synthesis or promoting cell differentiation . Additionally, we demonstrated that the melatonin synthesis/metabolism Index remained an independent prognosticator after including disease stage for adjustment in multivariable models, which implied that melatonin may influence prognosis through other biological mechanisms in addition to tumor carcinogenesis and proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, we found that higher content of melatonin in the tumor microenvironment was associated with less aggressive stage classification and favorable prognosis, which suggested that the melatonergic microenvironment may influence tumor carcinogenesis, prevent the formation of aggressive phenotypes, and therefore result in a decreased risk of death. This is consistent with previous observations that melatonin reduces the susceptibility of gastric mucosal cells to dietary carcinogens through enhanced DNA repair capacity, and inhibits cancer cell proliferation by decreasing DNA synthesis or promoting cell differentiation . Additionally, we demonstrated that the melatonin synthesis/metabolism Index remained an independent prognosticator after including disease stage for adjustment in multivariable models, which implied that melatonin may influence prognosis through other biological mechanisms in addition to tumor carcinogenesis and proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that the PI3K inhibitor LY294002, but not the ERK1/2 inhibitor U0126, abrogated the stimulatory effect of melatonin on adult spinal cord NSPCs. Melatonin has been shown to modulate the differentiation of NSPCs from adult mouse subventricular zone , while melatonin did not alter the differentiation of NSPCs from adult mouse spinal cord. Together, these results suggest the melatonin has different effects on the differentiation of NSPCs derived from adult mouse brain vs. spinal cord, and regulates the proliferation of NSPCs from the two origins through different signaling pathways.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies suggested that melatonin could regulate proliferation and differentiation of adult neural stem cells. Melatonin has been shown to enhance neurosphere formation of cultured neural stem cells from adult mouse subventricular zone, and to promote the differentiation of the stem cells toward neuronal cells [16,17]. Tocharus et al [18] demonstrated that melatonin increased the number of neurospheres from cultured adult rat hippocampal progenitor cells by activating the ERK signaling pathway.…”
Section: Abstract: Adult Spinal Cord Neural Stem Cells; Melatonin; Pimentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed antiaging and antineurodegenerative properties of melatonin are also driven by mitochondrial function enhancement and the activation of prosurvival pathways . Mitochondrial boost through melatonin may contribute to the neuroprotective and resilience‐promotor effects of this indoleamine. Regarding prosurvival pathways, it is known that melatonin activates the PI3K/Akt signaling pathway .…”
Section: Discussionmentioning
confidence: 99%